Ethical and Civilizational Perspectives on Digital Technology and Social Value: A Conceptual Review - Johar, Siti Sarawati; Husaini, Nazatul Amira; Kamil, Nazirah Aliah Mohd; Heng, Fong Li; Zaidi, Nur Diana Ilyana Muhammad; Hoong, Lee Poh; Li, Lim Wei; Jian, Lin Wei; Luo, Lue Zhen (CV. Literasi Indonesia, 2025)
The rapid evolution of digital technology has profoundly transformed how humans interact, construct values, and interpret civilization. This article explores the ethical and civilizational challenges posed by digital media through a conceptual literature review. It focuses on critical issues such as privacy, misinformation, algorithmic bias, and the impact of artificial intelligence (AI) on human values and cultural heritage. The discussion is framed using three ethical approaches: consequentialism, deontology, and virtue ethics. Strategic responses are proposed, including early digital ethics education, cultural preservation via modern platforms, and the enforcement of ethical technology policies. The article also addresses challenges such as social media addiction, cyberbullying, and uncontrolled technology use, which contribute to the erosion of social values and cultural identity. Ultimately, the article calls for a collective effort involving government, educational institutions, content creators, and society to cultivate a digital ecosystem that is not only advanced but also civilized and deeply human.